Exploring Understandings of Sexuality Among “Gay” Migrant Filipinos Living in New Zealand - Adams J; Manalastas EJ; Coquilla R; Montayre J; Neville S (SAGE Publications Inc)
Ethnicity, sexuality, and health are inextricably linked. This study reports on individual interviews carried out with 21 “gay” migrant Filipinos living in New Zealand to understand sexual identity and identify how they manage the disclosure of their identity. The participants provided both simple and complex accounts of sexuality. For many, these aligned with Western notions of how gay and bisexual are understood as categories; but for others, their understandings and use of such terms was influenced by Filipino cultural and contextual meanings. This included the use of “gay” as a catch-all category, including for those who identify as transgender. Active and careful management of their diverse identities was reported by participants. While disclosure to family was reasonably common, this was couched in terms of sexuality being tolerated rather than fully accepted. Disclosing identity was comparatively easier in New Zealand, but nonetheless there was active control over disclosure in some work and medical situations. Such findings add a degree of complexity within health promotion and public health, as identity cannot be regarded as static and common understandings do not exist. However, the strong community orientation and relative openness of “gay” Filipinos in relation to sexuality and gender afford opportunities for targeted interventions among this group.
Keywords: 1302 Curriculum and Pedagogy; 1608 Sociology; 1699 Other Studies in Human Society